Assessment of Lemon Juice Starter Addition on Secondary Fermented Soy Sauce - Yun-Hsi Chang; GiGi Chin Wen Lim; Ju-Yun Chien; Lu-Sheng Hsieh; Shinn-Dar Wu; Jhih-Ying Ciou (Fermentation, 2022)
Soy sauce is one of the most popular ingredients for delicious cuisines across the world, and it is made via various fermentation processes using wheat and soybeans. The purpose of this study was to add a lemon juice starter into secondary fermentation soy sauce to produce a new flavor of soy sauce to meet current health awareness and innovation market trends. The results showed that the lactic acid bacteria of the A group (soy sauce/starter culture ratio of 3:1) gradually decreased from 9.89 to 8.32 log CFU/mL by the seventh day, and then to 5.39 log CFU/mL by the 30th day, while they were not detected by the 60th day. Meanwhile, those of the B group (soy sauce/starter culture ratio of 1:1) showed a decrease from 10.39 to 8.58 log CFU/mL by the seventh day, and then to 5.39 log CFU/mL by the 30th day and 4.43 log CFU/mL by the 60th day, while they were not detected by the 90th day. As for yeast, the A group showed a decrease from 10.83 to 9.29 log CFU/mL (or 10.25 to 9.27 log CFU/mL for the B group) by the seventh day. Yeasts were not detected after 30 days in either the A or B group. The acidity and salinity of the lemon-flavored sauce was maintained after secondary fermentation. Sensory evaluation showed that the soy sauce with a lemon juice starter was accepted by consumers and obtained a better result than commercial soy sauce. In conclusion, secondary fermentation with starters contributes to the flavor quality of sauce products. Fruit juice is adjustable in terms of the acidity and salinity of the soy sauce and produces good flavor after secondary fermentation whenever it acts as a starter. The fact that customers favored the innovative lemon-flavored soy sauce indicates that this study is on the right trend.